Century Enterprise: Pee-Cut Machine / Muhammad Aniq Hazman Hairozie ...[et al.] - Hairozie, Muhammad Aniq Hazman; Hairuddin, Nurul Islah; Zulhakim, Afiq Affar; Mohd Sabri, Luthfi (2019)
Century Enterprise offers a product that combines two functions in a machine which are peeling and cutting. By this combination, Pee-Cut Portable Machine was made as an idea to ease people's activities in daily life. Household areas is a place that was surveyed which 63.6% from 70 respondents facing difficulties in cutting and peeling fruit for their daily uses. The major problem is the difficulty in peeling and cutting manually which is tiring and taking your time if you are inexperienced. Next, sharp tools as knives that were used in cutting and peeling can also give harms to people where danger is everywhere. So, by combining peeling and cutting, those difficulties are slowly will be easier and dangers can be avoided.